Anais Dos Workshops Do v Congresso Brasileiro De Informática Na Educação (CBIE 2016) 2016
DOI: 10.5753/cbie.wcbie.2016.751
|View full text |Cite
|
Sign up to set email alerts
|

A utilização do WhatsApp como ferramenta de comunicação didático-pedagógica no ensino superior

Abstract: The paradigm shift in education brings new challenges for teachers like the inclusion of mobile technologies in the classroom. Startign from this context, the article describes the application of an experiment with two different topics of higher education in Computer courses at the Federal University of Bahia: Laboratory of Informatcs in Education and Human-Computer Interaction. This experience aimed to integrate WhatsApp application as didactic and pedagogic communication tool to help the mediatization of kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
2
0
8
Order By: Relevance
“…Researchers have already observed that WhatsApp, being an easy access tool for most, can contribute to the communication between teachers and students, bringing integration and promoting debates about what they are studying [29].…”
Section: Whatsapp Messengermentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have already observed that WhatsApp, being an easy access tool for most, can contribute to the communication between teachers and students, bringing integration and promoting debates about what they are studying [29].…”
Section: Whatsapp Messengermentioning
confidence: 99%
“…WhatsApp was used in Philosophy in Technical Education, Physics in High School, Distance Gamification with teachers and as support for a course in undergraduate course. All the reports dealt with the fact that the groups formed in WhatsApp were effective, bringing more motivation, integration of the students and satisfaction in the debates [29].…”
Section: Whatsapp Messengermentioning
confidence: 99%
“…Uma das principais vantagens deste aplicativo é a sua sincronização com a lista de contatos, não sendo necessário memorizar nome de usuário e senha, bastando adicionar ou ter os números salvos nos contatos do celular (Alencar et al, 2015). O WhatsApp é uma ferramenta utilizada por uma boa parte dos alunos, se não todos, podendo facilitar o processo de comunicação entre os alunos e professor e também entre os próprios alunos, podendo criar um cenário propício para debates sobre diversos temas das disciplinas (Paiva et al, 2016). Honorato & Reis (2014, p. 3) afirmam que "para os alunos as vantagens do aplicativo WhatsApp são de passar informações sobre as matérias, tirar dúvidas sobre conteúdos, tarefas ou trabalhos".…”
Section: Tecnologias Móveis E Whatsappunclassified
“…Como o foco da atividade é o amigo secreto de elogios, e não o Whatsapp, a expectativa é que os alunos possam aprender a usar a ferramenta de comunicação de um modo mais transparente. Além disso, a criação do grupo de Whatsapp para a turma poderá servir como instrumento pedagógico (de Paiva et al, 2016), por meio do qual os participantes do grupo poderão compartilhar seus trabalhos e ajudar seus colegas em dúvidas relacionadas com o curso. Eu melhor.…”
Section: O Programa Propostounclassified